1996
DOI: 10.1016/s0092-8674(00)81392-6
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor Protein Shc Couples a Class of Integrins to the Control of Cell Cycle Progression

Abstract: We provide evidence that a class of integrins combines with the adaptor Shc and thereby with Grb2. Coimmunoprecipitation and mutagenesis experiments indicate that the recruitment of Shc is specified by the extracellular or transmembrane domain of integrin alpha subunit and suggest that this process is mediated by caveolin. Mutagenesis and dominant-negative inhibition studies reveal that Shc is necessary and sufficient for activation of the MAP kinase pathway in response to integrin ligation. Mitogens and Shc-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
628
7

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 711 publications
(672 citation statements)
references
References 47 publications
37
628
7
Order By: Relevance
“…Recent studies supporting the second possibility have shown that engagement of a subset of b 1 and a v integrins by ®bronectin stimulates the MAP kinase pathway and cell cycle progression via Shc; conversely, engagement of di erent integrins by other extracellular glycoproteins not linked to Shc, does not activate the MAP kinase pathway, and leads to cell cycle exit and apoptosis (Wary et al, 1996). Therefore, the array of glycoproteins displayed on a cell's surface determines the particular intracellular growth pathways that are stimulated, and it is thus critically important in sustaining normal cellular growth characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies supporting the second possibility have shown that engagement of a subset of b 1 and a v integrins by ®bronectin stimulates the MAP kinase pathway and cell cycle progression via Shc; conversely, engagement of di erent integrins by other extracellular glycoproteins not linked to Shc, does not activate the MAP kinase pathway, and leads to cell cycle exit and apoptosis (Wary et al, 1996). Therefore, the array of glycoproteins displayed on a cell's surface determines the particular intracellular growth pathways that are stimulated, and it is thus critically important in sustaining normal cellular growth characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…A number of signaling proteins have been found to be associated with the focal adhesion complexes suggesting the involvement of integrin engagement in the activation of signaling pathways. It is now generally accepted that the activation of ERK in response to integrin ligation requires Ras signaling Wary et al, 1996). Evidence is presented that certain integrins such as the laminin receptor a 6 b 4 , the lamin/collagen receptor a 1 b 1 , the ®bronectin receptor a 5 b 1 and the vitronectin receptor a v b 3 are linked to the RAS-ERK signaling pathway by the adaptor protein Shc (Wary et al, 1996;Giancotti, 1997).…”
Section: Role Of Integrins In Cell-proliferation Signaling Pathwaysmentioning
confidence: 99%
“…It is now generally accepted that the activation of ERK in response to integrin ligation requires Ras signaling Wary et al, 1996). Evidence is presented that certain integrins such as the laminin receptor a 6 b 4 , the lamin/collagen receptor a 1 b 1 , the ®bronectin receptor a 5 b 1 and the vitronectin receptor a v b 3 are linked to the RAS-ERK signaling pathway by the adaptor protein Shc (Wary et al, 1996;Giancotti, 1997). Shc is an SH2 and phosphotyrosine binding (PTB) domain adaptor protein which links tyrosinephosphorylated signal transducers to Ras (Pawson, 1995).…”
Section: Role Of Integrins In Cell-proliferation Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, previous studies showed that expression of a v b 3 integrins promoted cellular uptake via caveolae-mediated endocytosis and that, a v b 5 expression facilitated clathrin-mediated endocytosis. [39][40][41] As the binding affinity of cRGD with a v b 3 is 10 times stronger than that with a v b 5 , it might be reasonable that caveolae-mediated endocytosis was a dominant process in the cellular uptake of cRGD-PEG-PAsp(DET) micelles. 42 In contrast to clathrin-mediated endocytosis, the internalization pathway via caveolae-mediated endocytosis is known to bypass degradative organelles and not to be associated with a decrease in pH.…”
Section: Discussionmentioning
confidence: 99%